New Eudesmane-Type Sesquiterpene Glycosides from the Leaves of Aster koraiensis - Ji-Young Kim; Young Hye Seo; Im-Ho Lee; He Yun Choi; Hak Cheol Kwon; Jung-Hye Choi; Jun Lee; Dae Sik Jang (Plants, 2020)
Four new eudesmane-type sesquiterpenoids, (1R,5S,6R,7S,9S,10S)-1,6,9-trihydroxy-eudesm-3-ene-1,6-di-O-β-d-glucopyranoside (1), (1R,5S,6S,7R,9S,10S)-1,6,9,11-tetrahydroxy-eudesm-3-ene-1,6-di-O-β-d-glucopyranoside (3), (1R,5S,6R,7S,9S,10R)-9-O-(Z-p-coumaroyl)-1,6,9-trihydroxy-eudesm-3-ene-6-O-β-d-glucopyranoside (6), and (1R,5S,6R,7S,9S,10R)-9-O-(E-feruloyl)-1,6,9-trihydroxy-eudesm-3-ene-6-O-β-d-glucopyranoside (7), were isolated from a 95% EtOH extract of the leaves of Aster koraiensis by repeated chromatography. Moreover, three sesquiterpenoids (2, 4, and 5) and two caffeoylquinic acids (8 and 9) having previously known chemical structures were isolated during the isolation procedure. The four new compounds (1, 3, 6, and 7) were elucidated by spectroscopic data (1D- and 2D-NMR, MS, and ECD) interpretation and hydrolysis. Moreover, the absolute configurations of 2, 4, and 5 were determined for the first time in this study. The compounds isolated were tested for their viability on nitric oxide (NO) and prostaglandin E2 (PGE2) production on LPS-stimulated RAW 264.7 cells. Among them, only 7 presented weak inhibitory effects on both NO and PGE2 production.